Screening of Problem Behavior Syndrome in Adolescents - Corchado, A. I.; Martínez-Arias, R. (Child & adolescent social work journal, 2022)
Adolescence has received particular attention given its unique risk factors, which contribute to the onset and progression of problem behaviour and its development with varying levels of seriousness. Although much adolescent problem behaviour is exploratory, a screening tool is required to identify early problem behaviour, to enable the use of preventive strategies to prevent more serious or persistent behaviour. The problem behaviour frequency scale developed by Farrell et al. (2000) was adapted and validated for this purpose. Method: A sample of Spanish adolescents was obtained comprising 508 subjects, made up of two groups: 318 in the study group (62.7%) and 189 in the comparison group (37.3%). The sample was made up of 62.9% males and 37.1% females, aged between 12 and 18. Various structural models were evaluated and the evidence for reliability, structural validity, sensitivity and specificity was calculated. A cut-off point was established for diagnosis, and differences between case and control groups were identified. Result: The bifactor model obtained the best fit, affirming the hypothesis on unidimensionality of PBFS and supporting the concept of problem behaviour syndrome. Discussion: Results suggest that PBFS is a reliable and valid instrument for identifying problem behaviour